High Spatial Resolution BOTDA Based on Deconvolution and All Phase Digital Filtering - Peng, Jiaxin; Wang, Tao; Zhang, Qian; Ge, Xiaopeng; Zhu, Yaqi; Zhang, Yongqi; Zhang, Jianzhong; Li, Jian; Zhang, Mingjiang (IEEE sensors journal, 2024)
Brillouin optical time-domain analysis (BOTDA) technology plays an important role in distributed monitoring fields. However, the signal-to-noise ratio (SNR) is often degraded in the process of improving the sensing spatial resolution. Therefore, we propose a high spatial resolution BOTDA demodulation scheme based on a deconvolution algorithm complemented by all phase discrete Fourier transform (APDFT) digital filter. Initially, deconvolution algorithm is employed to improve the spatial resolution of the system. Subsequently, APDFT is used to filter out the noise in the signal, thereby improving the SNR while maintaining high spatial resolution. The results show that the sensing spatial resolution is optimized to 43 cm under a 40 ns pulsewidth in a 5.1 km sensing fiber and an enhancement in SNR by 6.5 dB is achieved compared to without denoising. The proposed scheme has a capability to achieve a heightened spatial resolution without upgrading the hardware devices of the BOTDA system.